Gender equality and the shifting gap in female-to-male prison admission rates - McLaughlin, Heather (Criminology, 2022)
Although women have made dramatic gains toward equality with men over the past century, this progress has occurred alongside tremendous growth in U.S. incarceration rates. Extending prior research on sex differences in offending, we turn our attention to punishment by exploring how gender equality in education, work, and politics is associated with disparities in annual prison admissions. Using pooled cross-sectional data for U.S. states from 1983 to 2010, we conduct a series of fixed-effects regressions to estimate the ratio of female-to-male annual prison admission rates, as well as sex-specific rates, disaggregated by violent, property, and drug crimes. We find partial support for the ameliorative hypothesis, which predicts that increasing gender equality will decrease female incarceration rates relative to male rates. For one of our three measures of gender equality - the sex gap in educational attainment - we find that greater equality is associated with a widening of the sex gap in incarceration rates, particularly for property offenses. We explore the implications of these findings in relation to existing theories of gender, crime, and punishment.